1995
DOI: 10.1002/mc.2940130203
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of O6‐methylguanine‐DNA methyltransferase to monofunctional alkylating‐agent resistance in human brain tumor—derived cell lines

Abstract: The DNA repair protein O6-methylguanine-DNA methyltransferase (MGMT) has been implicated in resistance of human brain tumors to alkylating agents. We observed that 14 human medulloblastoma- and glioma-derived cell lines differ in sensitivity to the methylating agent N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), as shown by their 28-fold range in 10% survival dose (LD10). By using the substrate analogue inhibitor O6-benzylguanine (O6-BG), we showed that the contribution of MGMT to resistance varies widely, as ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 39 publications
8
38
0
Order By: Relevance
“…Although the cytotoxicity of chloroethylating agents and methylating agents can be attributed to quite different DNA lesions, both depend upon initial adduct formation at the O 6 -position of guanine (9,55,56). Several preclinical and clinical studies have strongly suggested that the DNA repair enzyme MGMT, with reverse alkylation at the O 6 -position of guanine, plays an important role in cellular resistance to chlorethylation or methylation damage at the O 6 -position of guanine DNA (10,(13)(14)(15)(16)(17)(18)26,(57)(58)(59)(60)(61)(62). In human cancer, the MGMT gene is not commonly mutated or deleted, and loss of MGMT function is most frequently due to epigenetic changes, particularly promoter hypermethylation (22,28,63), which cause MGMT transcriptional silencing in cells with defective O 6 -methylguanine repair (22,28,64,65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cytotoxicity of chloroethylating agents and methylating agents can be attributed to quite different DNA lesions, both depend upon initial adduct formation at the O 6 -position of guanine (9,55,56). Several preclinical and clinical studies have strongly suggested that the DNA repair enzyme MGMT, with reverse alkylation at the O 6 -position of guanine, plays an important role in cellular resistance to chlorethylation or methylation damage at the O 6 -position of guanine DNA (10,(13)(14)(15)(16)(17)(18)26,(57)(58)(59)(60)(61)(62). In human cancer, the MGMT gene is not commonly mutated or deleted, and loss of MGMT function is most frequently due to epigenetic changes, particularly promoter hypermethylation (22,28,63), which cause MGMT transcriptional silencing in cells with defective O 6 -methylguanine repair (22,28,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…One of the key factors controlling sensitivity to O 6 alkylating agents including TMZ in tumors is therefore considered to be the action of MGMT (10)(11)(12)(13). Indeed, several investigators have reported that, in malignant gliomas, MGMT expression is closely correlated with experimental and clinical resistance to these chemotherapeutic agents (14)(15)(16)(17)(18). Furthermore, recent studies have indicated that, since MGMT protein loss may be a result of promoter hypermethylation, methylation of the MGMT promoter is significantly correlated with clinical outcome in malignant glioma patients treated with alkylating agents including TMZ (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel sensitivity was determined by clonogenic assay as described previously (Bobola et al, 1995a). Brie y, 12-well trays were inoculated with 2 mL of medium containing 750 cells and incubated overnight.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…For biphasic curves, LD 10 re ects D 37 for each subpopulation and the fraction of cells in each subpopulation. Graphical derivation of D 37 and LD 10 from survival curves is presented in detail in Bobola et al (1995a).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation